Media Construction of Gender: Framing Analysis of Rape Cases in Mass Media - ALI IMRON (Jurnal Studi Pemerintahan, 2013)
Construction of the printed media which tends to dramatize and blow up the reporting of rape cases has in fact discredited the rape victim, resulting in gender bias. This is due to the fact that media present the news content concerning on the victim and the perpetrator in imbalanced reporting, in that the victims are scrutinized from diverse facets. This paper analyze the coverage of printed media in rape cases by means of framing analysis. The result shows that printed media coverage generally goes beyond the rape case itself as the victim’s identity and images of the incident are also revealed. The using of visual image(victim’s image) is probably aimed to present an overview on the fact or the truth from the media viewpoint. This presentation, however, obscures the differences between factual and fictional reality and this might lead to different interpretation on the readers’ side. Furthermore, inappropriate reporting might become the society’s reference concerning on the modus operandi, in that the society learn or imitate the aspects they once did not know of. Visual image will create a second rape by the media toward the victim, in addition to the stereotyping developed in public, which often brings out psychological impact to the victim and the family. This is called the third rape.